Toxicidade e potencial antitumoral do Tonantzitlolone B, um diterpeno de Stillingia loranthaceae (Euphorbiaceae) - Abrantes, Renata de Albuquerque (2018)
Natural products represent a rich source of bioactive compounds for the treatment of various diseases. Among the natural products with antitumor potential are diterpenes, secondary metabolites of the terpenoid class which have 20 carbon atoms in their structure. Tonantzitlolone B (TNZ-B) is a rare diterpene of the class of flexibilenes that presents reports of antitumor activity in vitro in different cell lines. However, there is no evidence in the literature regarding its toxicity and antitumor activity in vivo. Thus, the present work aimed to evaluate the toxicity and antitumor potential in vivo of TNZ-B in the Ehrlich ascitic carcinoma (CAE) model, as well as to investigate possible mechanisms of action involved in this effect. Initially, the acute pre-clinical toxicity of TNZ-B in mice was evaluated intraperitoneally (i.p.). LD50 (50% lethal dose) was estimated at 25 mg / kg, considering Guide n. 423 from the Organization for Economic Co-operation and Development (OECD), which indicates high toxicity. Also, in behavioral pharmacological screening, few TNZ-B-induced effects were observed, such as abdominal writhing and loss of corneal and atrial reflex, which disappeared shortly after treatment. The micronucleus test was used to evaluate the genotoxicity of TNZ-B. It was observed that this diterpene (3.0 or 6.0 mg / kg, i.p.) did not induce an increase in the number of micronucleated erythrocytes, suggesting low genotoxicity. In the CAE model, TNZ-B (1.5 or 3.0 mg / kg, ip, seven consecutive days of treatment) was found to reduce tumor volume, tumor mass and total tumor cell parameters (p < 0.05). To study the mechanism of antitumor action of TNZ-B, the antiangiogenic and antioxidant effects were evaluated. TNZ-B (3 mg / kg) reduced the microdensity of the vessels in the peritoneum of the animals (p <0.05), which suggests antiagiogenic action. Then, considering the vast role of oxidative stress in tumor propagation, the effect of TNZ-B was assessed by means of the fluorometric test with the 2,7-dichlorofluorescein diacetate (DCFH-DA). A reduction in oxidative stress level (p <0.05) was observed after treatment with TNZ-B (3.0 mg / kg), suggesting antioxidant effects. In addition, TNZ-B (3.0 mg / kg) was shown to reduce nitric oxide (NO) production (p <0.05), a key mediator involved in growth, angiogenesis and tumor metastasis. In the evaluation of toxicity in CAE transplanted animals submitted to seven days of treatment with TNZ-B (3.0 mg / kg, i.p.), only a reduction of red blood cell count was observed, indicating that TNZ-B has low biochemical and hematological toxicity. On the other hand, TNZ-B induced an increase in the indexes of the liver, spleen, kidneys and heart, which should be better evaluated through histopathological analysis. The data presented, together, suggest that TNZ-B has antitumor activity by exerting antiangiogenic action through modulation of oxidative stress and reduction of nitric oxide levels.